CEO Pay Disclosure and Within-Firm Wage Inequality - Agata Maida; Vincenzo Pezone (Institute of Labor Economics (IZA), 2024)
We analyze the effect of CEO pay disclosure on wage distribution by exploiting a 1998 reform requiring Italian publicly listed companies to disclose top executives' compensation. In firms where CEOs disclose high total compensation, the top 5 percent and 1 percent of the within-firm wage distribution rise substantially. Instead, the effect on average wages is small and only marginally significant. As a result, wage inequality increases. These effects are stronger for workers with low experience or located in the main region of the firm's operations. Moreover, they are driven by changes in workers' bargaining power, rather than by sorting.
Keywords: J31; D63; D9; M12; 330; CEO compensation; wage disclosure; income inequality; wage bargaining